Evaluación de crianza de pollos COBB 500 en costa y sierra ecuatoriana y su efecto en parámetros productivos - Guaillas Obaco, José Benigno (2024)
This study evaluated the effect of the coastal and highland regions in Ecuador and sex on productive parameters (weight gain, feed intake, feed conversion ratio, carcass yield) and the benefit/cost ratio in Cobb 500 chickens. The research was conducted in Chone and Loja, with a total of 320 chickens, under a completely randomized design with an alpha value of 0.05, using four treatments and repetitions, distributed with 160 chickens at each site. The results showed that sex significantly influenced weight gain during the first three weeks, with females in the first week T4 (p<0.0085) and males in the second week T3 (p<0.0099) and third week T1 (p<0.0089). In terms of feed intake, males stood out in the third week T1 (p<0.0001) and in the fourth week T3 (p<0.0012). Feed conversion ratio varied, with females T2 excelling in the first week (p<0.0308), while males T1 excelled in the second week (p<0.0074). However, the overall accumulated results showed no significance in the measured variables, including carcass yield and cost-benefit ratio, although T1 outperformed the other treatments with values ranging between one and two cents of a dollar. It is concluded that sex showed influence only during the first three weeks of rearing, and the region does not significantly influence the productive parameters of the chickens, indicating that the production of Cobb 500 chickens is feasible in both regions in Ecuador.